Electrochemical grafting of poly(glycidyl methacrylate) on a carbon-fibre surface. Issue 18 (12th March 2020) - Hu, Changtong; Ruan, Ruyu; Wang, Wenshun; Gao, Aijun; Xu, Lianghua
Abstract : In this work, glycidyl methacrylate (GMA) was polymerised and grafted onto the surface of carbon fiber (CF) by using electrochemical grafting to improve the interfacial properties between the fibre and epoxy resin. Abstract : In this work, glycidyl methacrylate (GMA) was polymerised and grafted onto the surface of carbon fiber (CF) by using electrochemical grafting to improve the interfacial properties between the fibre and epoxy resin. The optimised conditions for electrochemical grafting and the reaction mechanism were also investigated. Results showed that GMA was covalently grafted to the CF surface by the assistance of aluminium chloride, which is a good electrolyte for electrochemical grafting. The GMA grafting ratio on the CF surface increased with electrolyte concentration and reaction time, and an optimal current intensity for the electropolymerisation was determined. On the basis of the strong correlation between the grafting ratio and the carboxyl content in the CF, a two-step mechanism of electrochemical grafting on the CF surface was proposed: first, the surface of CF was anodised to produce oxygen-containing functional groups, mainly including COOH, OH and CO. Next, when CF was used as the anode in the electrical grafting reaction, the COOH on the surface of CF would lose electrons and then remove carbon dioxide to generate carbon radicals on the surface of CF. The carbon radical would attack the carbon–carbon double bond in GMA to initiate the radical polymerisation of GMA monomers and graft polymers would be formed on the CF surface. Compared with untreated CF, the interfacial shear strength (IFSS) test proved the improvement of the interface adhesion of the modified carbon fibre (mCF) composites. This work provided a controllable electrochemical approach that could simply and quickly graft poly(glycidyl methacrylate) (PGMA) on the surface of CF.